IMAGINATION AND LEARNING: THE ROLE OF CREATIVE THINKING IN PRIMARY EDUCATION - Natalia Posada Restrepo; Cristina Eugenia Orozco Jiménez (LÍNEA IMAGINARIA, 2025)
This article delves into the relevance of creative thinking in the education of primary school students. It proposes pedagogical strategies that foster its development and offers recommendations for effectively integrating it into the classroom. It highlights the need to review how the concept of creativity has changed, since, although its importance is recognized, its practical application in curricula remains quite limited, especially at the most basic educational levels. Through an analysis of various research projects and the main theories on creative thinking, the article emphasizes that a deep understanding of this skill is crucial for fostering more complex competencies in students. It concludes that fostering creativity in the classroom requires a purposeful educational intervention, with teachers trained in this approach and a significant transformation of traditional curricula. Only in this way can we prepare future generations to face the challenges of a constantly evolving society with originality, resilience, and critical thinking.